0459 The First Step of a Triaged Stepped-Care Delivery of CBTI: A Preliminary Report from the RESTING Study. (25th May 2022) - Manber, Rachel; Kim, Jane; Simpson, Norah; Tully, Isabelle; Tutek, Joshua; Dietch, Jessica; Gumport, Niki; Rosas, Lisa; Zulmann, Donna; Palaniappan, Latha
Abstract: Introduction: Both online and therapist-led cognitive behavioral therapy for insomnia (CBTI) are effective. However, little is known about the optimal combination and sequence to maximize both access and effectiveness. The RESTING study is a randomized controlled trial assessing the effectiveness of a triaged stepped care approach (STEPPPED-CARE) to delivering CBTI that utilizes a simple five-item Checklist to determine which patients should start treatment with online versus therapist-led CBTI. Methods: Adults 50 years and older (N=222; age = 63.1 (SD=8.2); 74% female) with insomnia disorder who met the study's broad eligibility criteria were randomized to STEPPED-CARE (N=112) or to ONLINE-ONLY CBTI (N=110). Participants in the STEPPED-CARE arm who responded yes to any Checklist item (Checklist Yes) received therapist-led CBTI (N=61); the rest (Checklist NO) received the online CBTI program Sleepio (N=62). All participants in the ONLINE-ONLY arm received Sleepio. Randomization was stratified by Checklist (Yes/No). We used mixed effects models with an Arm by Checklist by Time interaction to determine the effect of STEPPED-CARE on insomnia severity two months after randomization, using the Insomnia Severity Index (ISI). Results: A mixed effects model revealed an Arm by Checklist by Time interaction (p=0.013). Post-hoc analyses within stratum revealed that within the Checklist Yes stratum, participants assigned to STEPPED-CARE (all received therapist-led treatment) experienced significantly greater reduction in ISI (from 16.2 (SD=1.2) to 11.6 (SD=2.1)) than those assigned to ONLINE-ONLY (from 16.2 (SD=1.2) to 13.7 (SD=1.4); p=0.007, d=0.22). Among those in the Checklist No stratum, there was no Arm difference in ISI change. The combined mean ISI in the Checklist No group was 14.8 (0.8) at baseline and 11.2 (0.8) at 2 months. Overall, remission of insomnia (ISI<8) was attained by 23% of those in STEPPED-CARE and 15% of those assigned to ONLINE-ONLY. Conclusion: Results support the efficacy of the first step of a triaged stepped care approach to CBTI among middle age and older adults with insomnia disorder. Given minimal exclusion criteria, results from the current trial are generalizable to individuals with comorbidities and those who use hypnotics, offering a way to triage patients to digital or therapist-led CBTI effectively and efficiently. Support (If Any): R01AG057500